Bismuth(III)-catalyzed cycloisomerization and (hetero)arylation of alkynols: simple access to 2-(hetero)aryl tetrahydrofurans and tetrahydropyrans - Nakate, Ashwini K.; Pratapure, Madhukar S.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2018)
2-(Hetero)aryl tetrahydrofurans and tetrahydropyrans were successfully synthesized using Bi(OTf)(3)-catalyzed hydroalkoxylation (cycloisomerization) of alkynols (via 5 or 6 exo-dig cyclization) and intermolecular (hetero)arylation. This reaction involves a highly efficient cascade process, where initially the alkynol undergoes a cycloisomerization step via activation of the triple bond and generates the oxocarbenium ion, which subsequently participates in the (hetero)hydroarylation step with electron-rich arenes. Simple to complex suitably functionalized alkynols (4-pentyn-1-ols and 5-hexyn-1-ols) and electron-rich aromatic compounds were found to be reliable substrates in this cascade transformation and furnished a wide range of oxygen heterocycles. This practical tandem process provides a means to build libraries related to pharmacologically active molecules and natural product like scaffolds.

Bismuth(iii)-catalyzed bis-cyclization of propargylic diol-esters: a unified approach for the synthesis of [5,5]- and [6,5]-oxaspirolactones - Kambale, Digambar A.; Borade, Balasaheb R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2021)
Herein we disclose an unprecedented intramolecular cascade strategy for the construction of alpha,beta-unsaturated [5,5]- and [6,5]-oxaspirolactones that capitalizes on the pi-electrophilic Lewis acid-catalyzed 5-exo-dig or 6-exo-dig mode of cyclization of propargylic diol esters, followed by dehydration and spirolactonization steps. Moreover, semi-protected substrates also delivered the respective oxaspirolactones with the same ease and in appreciable yields under optimal reaction conditions.

Bi(III)-catalyzed synthesis of substituted furans from hydroxy-oxetanyl ketones: application to unified total synthesis of shikonofurans J, D, E, and C - Kataria, Priyanka; Sahoo, Shubhranshu Shekhar; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
We report an improved synthetic protocol for hydroxymethyl-derivedpolysubstituted furans employing Bi-(III)-catalyzed dehydrative cycloisomerizationof alpha-hydroxy oxetanyl ketones. This procedure provides rapidaccess (within 5 min) to highly substituted furans with exceptionalfunctional group diversity, excellent yields, generality, scalability,and operationally simple reaction conditions. Further, it demonstratedthe utility of this method in the first enantioselective total synthesisof furyl-hydroquinone-derived biologically potent natural productsshikonofurans J, D, E, and C in seven linear steps, starting fromreadily available building blocks of 2,5-dihydroxy acetophenone and3-oxetanone employing chiral-phosphoric acid (TRIP)-catalyzed asymmetricprenylation as a key step to induce the chirality.

Bismuth(III)-catalyzed cascade condensation of alkynyl alcohols with terminal alkynes: a facile construction of propargyl cyclic ethers - Pratapure, Madhukar S.; Kontham, Ravindar (Tetrahedron Letters, 2023)
Herein, we report a Bi(OTf)3-catalyzed cascade condensation between alkynols (particularly pent-4-yn-1ols and hex-5-yn-1-ols) and terminal alkynes (aryl alkynes) to facile access to diverse propargyl cyclic ethers (2 alkynyl tetrahydrofurans and 2 alkynyl tetrahydropyrans). This simple and efficient cascade transformation proceeds through initial intramolecular hydroalkoxylation of alkynols to give corresponding cyclic enol ethers (via exo-dig or endo-dig mode of ring-closure) followed by hydroalkynylation. Costeffective, naturally abundant, green Lewis acid catalysis, ambient reaction conditions, short reaction times, good substrate scope, and high yields are salient features of this strategy.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Alkynyl alcohols; Bismuth catalysis; Cascade condensation; Propargyl cyclic ethers; Terminal alkynes

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.